THE SPIRIT OF TRANSCENDENTALISM AND INDIVIDUALISM AS SEEN IN EMERSON’S SELF-RELIANCE - Rizki Februansyah (University of Muhammadiyah Purwokerto, 2008)
The article discusses transendentalism and inidvidualism as reflected from an essay “Self Reliance” written by Emmerson in 1841. In the American history, the writer is a big thinker with a dominant role in the development of intellectuality and spirituality. While reforming the religious system of American society that ignoring an intuition, his thought also indirectly inspires the concept of separation between state and church. With an interdisciplinary approach, it is found out that transendetalism of Emerson is a resistance to the morals of Christianity. It is also proved that the Individualism Emerson emphasized is caused by the condition of American society that had not shown their identity as a nation with freedom in all aspects of life.